Does GPS supervision of intimate partner violence defendants reduce pretrial misconduct? Evidence from a quasi-experimental study - Grommon, Eric L. (Journal of experimental criminology, 2017)
This research examines the effect global positioning system (GPS) technology supervision has on pretrial misconduct for defendants facing intimate partner violence charges.